An Empirical Analysis of the Impact of the China Free Trade Zone on the Level of Human Capital Based on the Asymptotic PSM-DID Model - Ruijun Xie; Rong Wang; Duolei Zhang (Discrete Dynamics in Nature and Society)
The article selects relevant data from 283 cities in China from 2000 to 2020 and verifies the impact of the establishment of free trade zones on human capital levels based on the asymptotic PSM-DID model. It is found that the establishment of FTZs can significantly contribute to the improvement of regional human capital levels, but the promotion effect has a certain lag. Finally, the article gives constructive suggestions based on the empirical results.